1958
DOI: 10.1099/00221287-18-1-58
|View full text |Cite
|
Sign up to set email alerts
|

The Heat Inactivation of Vaccinia Virus

Abstract: SUMMARY: Heat inactivation curves of vaccinia virus between 50' and 60' indicate that the virus is heterogeneous in its heat sensitivity. The proportion of heatresistant particles varies inversely with the temperature of exposure. The inactivation of heat-sensitive virus is temperature dependent and seems to be a first-order reaction, while the heat-resistant fraction is inactivated at a constant slow rate unrelated to temperature over the range 5Oo-6O0.The work reported here is part of a larger investigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
1

Year Published

1965
1965
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 9 publications
4
22
0
1
Order By: Relevance
“…Retrieving the various publications cited herein was one of the most difficult aspects of this survey. The literature obtained includes reports of the inactivation of a variety of non-enveloped [3][4][5][7][8][9][10][11]19,[23][24][25][26][27][28]39] and enveloped [1,6,12,[14][15][16][17][18]21,22,26,[29][30][31]33] viruses. As might be expected, those viruses considered a threat to food safety are somewhat more highly represented in the heat inactivation literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrieving the various publications cited herein was one of the most difficult aspects of this survey. The literature obtained includes reports of the inactivation of a variety of non-enveloped [3][4][5][7][8][9][10][11]19,[23][24][25][26][27][28]39] and enveloped [1,6,12,[14][15][16][17][18]21,22,26,[29][30][31]33] viruses. As might be expected, those viruses considered a threat to food safety are somewhat more highly represented in the heat inactivation literature.…”
Section: Resultsmentioning
confidence: 99%
“…Heat inactivation of viruses represents an important approach for mitigating the risk of viral contamination for food and drinking water protection [1][2][3][4][5][6][7][8][9][10], inactivation of vaccine viruses [11][12][13][14][15], inactivation of viruses of importance to agriculture and animal husbandry [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], and inactivation of viruses in blood products [31][32][33]. More recently, heat inactivation and more particularly high-temperature short-time (HTST) treatment have been evaluated as a barrier technology for mitigating the risk of introducing adventitious viral contaminants into biologics manufacturing processes through contaminated cell culture reagents [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Hahon and Kozikowski [8] determined the Δ H and Δ S of variola major virus in various buffers at temperatures from 40°C to 55°C. Previous studies with vaccinia virus demonstrated that vaccinia virus has a range of Δ H values from 20,000 to 90,000 calories per mole [12]. Variola major virus has a Δ H values in the range described by Kaplan [12].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on VACV have traditionally focused on virus viability and potency of stored vaccine preparations, while baculovirus research is agriculturally based with a centralized focus on the improvement of formulation and insecticide performance (Falcon, 1969;Kaplan, 1958;Roberts and Hope, 2003). These divergent research topics and wide variety of experimental conditions have resulted in many datasets that are difficult to compare with one another.…”
Section: Discussionmentioning
confidence: 99%
“…Kaplan (1958) investigated the persistence of VACV and determined inactivation curves at temperature ranges between 50-60 °C. The results from this study demonstrated a rapid fall of infectivity followed by a complete inactivation at a much slower rate.…”
Section: Vacvmentioning
confidence: 99%